A Systematic Review of Blinatumomab in the Treatment of Acute Lymphoblastic Leukemia: Engaging an Old Problem With New Solutions. Issue 10 (October 2021) - Halford, Zachery; Coalter, Carli; Gresham, Vanessa; Brown, Tabitha
Objective: To assess the current literature for blinatumomab in the treatment of adult and pediatric B-cell acute lymphoblastic leukemia (ALL). Data Sources: We conducted a PubMed (inception to December 11, 2020) and ClinicalTrials.gov systematic literature search using the following terms: blinatumomab, Blincyto, lymphoblastic leukemia, and bispecific T-cell engager . Study Selection and Data Extraction: All relevant published articles, package inserts, and meeting abstracts evaluating the use of blinatumomab in ALL were considered for inclusion. Data Synthesis: Blinatumomab, a first-in-class bispecific T-cell engager monoclonal antibody, facilitates cytotoxic T-cell activation and subsequent eradication of CD19-positive B cells. The confirmatory phase III TOWER trial demonstrated superior overall survival (OS) with blinatumomab compared with standard chemotherapy (7.7 months vs 4.0 months) in relapsed and refractory (R/R) B-cell ALL. In the phase II BLAST trial, blinatumomab achieved a complete measurable residual disease (MRD) response in 78% of evaluable patients, with a median OS of 36.5 months. Potentially life-threatening cytokine release syndrome and neurotoxicity occurred in approximately 15% and 65% of patients, respectively. Relevance to Patient Care and Clinical Practice: Following initial Food and Drug Administration approval in 2014, blinatumomab gained expanded approval in pediatric patients and in Philadelphia chromosome-positive R/R ALL. In 2018, blinatumomab became the first and only drug approved for the treatment of persistent MRD in any hematologic malignancy. Emerging data demonstrate promising efficacy with blinatumomab in specific ALL settings, including frontline therapy, as a bridge to transplantation, and in "chemotherapy-free" combination regimens. Conclusions: Blinatumomab provides a paradigm-shifting treatment option; however, many questions surrounding optimal patient selection, sequencing, and cost-effectiveness remain.